Health Benefits from Renewable Electricity Sources: A Review - Susana Silva; Erika Laranjeira; Isabel Soares (Energies, 2021)
Energy generation has had several negative health impacts over the last few decades, mainly due to air pollution. One of the ways to decrease such impacts is to increase energy generation through renewable energy sources (RESs). These sources have important health co-benefits that need to be taken into consideration. This topic has been included in the literature, but research is scattered. The goal of this article is to show the status of the literature on this topic. We performed a systematic literature review on the health co-benefits of RES use, depicting the state of the art of this literature, some common findings, limitations, and lines for future research. It is clear from our analysis that this literature remains scarce. We found 28 studies fitting the inclusion criteria. Results can be summed as follows: (1) wind and solar power are the most studied RES sources; (2) most studies are for the United States and developing countries are largely understudied; and (3) health benefit results vary widely according to site-specific conditions. Overall, the existing studies show significant health co-benefits from RES use, which are important to consider when performing cost–benefit analysis for energy projects. This is particularly relevant for policy-makers and energy investors.